The mediating role of fear of COVID‐19 in the relationship between intolerance of uncertainty and depression. (20th November 2020) - Voitsidis, Panteleimon; Nikopoulou, Vasiliki Aliki; Holeva, Vasiliki; Parlapani, Eleni; Sereslis, Konstantinos; Tsipropoulou, Virginia; Karamouzi, Panayiota; Giazkoulidou, Aikaterini; Tsopaneli, Nektaria; Diakogiannis, Ioannis
Abstract : Objectives: Living during the COVID‐19 pandemic is characterized by the emergence of great uncertainty surrounding multiple aspects of daily life. This study explored the relationship between intolerance of uncertainty (IU) and depression, as well as the potential mediation effect of COVID‐19‐related fear. Design and methods: A cross‐sectional study was conducted through an online survey from 10 April until 13 April 2020, three weeks after a national lockdown had been imposed in Greece. The convenience sample used in this study consisted of 2, 827 adults. Participants voluntarily provided sociodemographic data and completed the following scales: the Intolerance of Uncertainty Scale (IUS‐12), the Fear of COVID‐19 Scale (FCV‐19S), and the Brief Patient Health Questionnaire (PHQ‐9) Depression Scale. Results: Participants appeared to be moderately depressed [ M = 14.75, SD = 4.52]. There was a significant indirect effect of IU to depressive symptoms ((.058), CI (0.051–0.066)). FCV‐19S was tested as a mediator in the relationship between IUS‐12 (independent variable) and PHQ‐9 (dependent variable). Partial mediation of fear of COVID‐19 was supported ((.54) (.41) = 13, CI (0.051–0.066), Sobel z‐value = 14.93). Conclusions: Depressive symptomatology affected study participants at a moderate level. IU was shown to be a significant predictor of depressive symptomatology with higher levels of IU being associated with more severe depressive symptoms. Fear of COVID‐19 partially mediated this association. The mediation effect may be explained by the uncertainty around COVID‐19‐related health issues, which are reflected in the FCV‐19S and cause worry and/or anxiety. Uncertainty related with other factors, such as the impact on the economy and education, not assessed by the FCV‐19S, may explain part of the relationship between IU and depressive symptoms that is not mediated by FCV‐19S. Practitioner Points: Intolerance of uncertainty is related to depressive symptomatology, and fear of COVID‐19 explains part of the relation. Fear of COVID‐19 indicates worry and anxiety related to health issues. Psychotherapeutic interventions enhancing individuals' capacity to endure uncertainty could be beneficial. Provision of simple and clear information by the authorities should be a priority issue.